Digital Transformation in Civic Education: Advancing Digital Citizenship through Values-Based Learning - A Conceptual Review - Muhammad Muslim Hidayatulloh; Winarno Winarno; Dewi Ika Sari; Nesliani Paotonan (International Journal of Research and Community Empowerment, 2026)
The fast growth of digital technology has changed how education works, including Civic Education, which helps make citizens responsible and involved in society. In today’s digital world, Civic Education has to not only use technology in teaching but also make sure that using digital tools is based on knowing what’s right, being responsible, and supporting democracy. This study looks at how changing to digital teaching methods in Civic Education can help students become better digital citizens by using a learning approach that focuses on values. The study uses a detailed review of existing research and ideas to gather information from articles, government policies, and real-world studies about digital change, civic education, digital citizenship, and teaching values. The research shows that using digital teaching methods like blended learning, flipped classrooms, project-based learning, and interactive digital tools can help students improve their civic skills, their ability to think critically about digital content, and their sense of responsibility online. It also shows that learning based on values helps students handle problems like fake news, divided opinions online, and shallow engagement with digital content. This study highlights the need for teachers to act as guides who encourage thinking and active learning, connecting civic values with digital activities. The ideas from this study help build better Civic Education programs that support digital citizenship and provide high-quality education, which connects to important goals like improving education (Goal 4), promoting peace and justice (Goal 16), and reducing inequality (Goal 10).